FTIR study of the photocatalytic degradation of gaseous benzene over UV-irradiated TiO2 nanoballs synthesized by hydrothermal treatment in alkaline solution - Zhu, Z.; Li, Xin Yong; Zhao, Q.; Qu, Z.; Hou, Y.; Zhao, L.; Liu, Shaomin; Chen, G. (Pergamon, 2010)
In this study, photocatalysts of TiO2 nanoballs were obtained via a hydrothermal treating of commercial P25 in alkaline solution, and then characterized with SEM, XRD, BET and surface photovoltage spectroscopy techniques. The UV-assisted photodegradation of gaseous benzene over P25 and the prepared TiO2 nanoballs was monitored by an in situ infrared technique. The results demonstrated that the prepared TiO2 nanoballs in anatase form were more active than commercial P25 in photocatalytic oxidation of gaseous benzene. The promoted activity of the hydrothermal-treated TiO 2 is attributed to the increasing specific surface area and larger band gap induced by the reduced crystallite size. The spectra of FTIR indicated that weakly adsorbed phenol was formed as the reaction progress. Hydroxyl groups on the surface of TiO2 nanoballs are able to react with photo-produced phenol, which is then retained on the catalyst surface leading to the progressive deactivation of the catalyst in the gas-solid system. © 2010 Elsevier Ltd. All rights reserved.